Remarks on neurocontrol of the hand and significance of afferent input - Šarabon, Nejc (Zdravniški vestnik, 2004)
This paper outlines some remarks on our understanding of motor control of the hand. It begins with current knowledge about motor behavior of prehension movements. It further highlights the distributed nature of the control system that integrates sensory information from the periphery, existing motor memory from subcortical centers, and information from diverse primary and secondary motor as well as sensory areas. It further explains the sequential nature of the processes like decision, planning computing and execution involved in neurocontrol of a purposeful hand motor task. In the successive part it stresses the importance of sensory input, in particular proprioceptive, for movement setting and guidance. It concludes by pointing out research concepts used to study roles of sensory information for modulating states of neurobiological systems. Finally, a novel method of whole hand electrical stimulation, which seems promising as a tool for studying sensory-motor integration mechanisms in human's hand, is explained and recent experimental data are provided.
Keywords: Aferentne poti; Afferent Pathways; električna stimulacija; Gibanje; Hand; Innervation; lokomocija; Motor Activity; Motor Neurons; Motorična aktivnost; Motorični nevroni; Movement; Physiology; Propriocepcija; Proprioception; Roka; živčna kontrola